Creating an environment for thriving: An ethnographic exploration of a British decentralised Olympic and Paralympic Sport Organisation. (September 2022) - Passaportis, Michael J.R.; Brown, Daniel J.; Wagstaff, Christopher R.D.; Arnold, Rachel; Hays, Kate
Abstract: Objectives: The aims of this study were to explore the features of the athletic environment that influence thriving within a British Olympic and Paralympic sport organisation and to understand the interconnectedness of these factors across a range of individuals and contexts. These aims were pursued within a decentralised organisation that was undergoing a leader-led cultural change strategy. Method: To develop an understanding of the environmental factors that facilitate athlete thriving, a 16-month ethnography was conducted. Data analysis consisted of reflexive thematic analysis of observational notes, reflexive diaries, and interview transcripts. The findings are presented in an ethnographic tale. Results: Alongside the complexities of implementing a culture change strategy across a decentralised organisation, the ethnographic tale details three key features of the athletic environment targeted by senior leadership to successfully influence the athletes' ability to thrive within their silos. Underpinning these factors are three interconnected themes of understanding, openness, and trust. Conclusions: This study demonstrates how empowering devolved leadership was impactful for organisational culture by reducing the homogeneity of leader-centric change initiatives. Further, harnessing an organisation-wide commitment to promoting relationships founded on understanding, openness, and trust can create athletic environments that facilitate thriving. Therefore, while a decentralised structure may present challenges for promoting a duty of care, it is possible to create an environment that supports athletes to thrive. Highlights: Ethnography of a British decentralised Olympic and Paralympic Sport Organisation. Thriving facilitated through an embracement of understanding, openness, and trust. Empowering subgroups and subcultures can lead to cohesion and thriving. Empowering devolved leadership can drive cultural change initiatives.